Attitudes toward Teaching Science at Teacher Training Colleges in Lao PDR - Souksomvang, Phoui; Tiengmany, Keo; Vilaythong, Thongloun; Padtha , Phayvanh; Nasoukhoum, Philavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This paper studies the teaching methods for Department of Natural Sciences of Teachers Training Colleges in Laos with the purpose: 1) to survey the opinions of teachers with respect to the relationship between the current teaching methods towards the results studied of students in Department of Natural Sciences of Teachers Training Colleges in Laos; 2) to find teaching methods that adapt to the realities and conditions of the education system in Lao PDR, specifically the teaching methods Department of the Natural Sciences of the Teachers Training Colleges. The sample group consisted of teachers who taught in Department of the Natural Sciences, as well as administrators and retired teachers at all 7 Teachers Training colleges like: Luang Namtha, Khangkai, Luang Prabang, Ban Keun, Savannakhet, Pakse and Saravane Teachers Training Colleges. The study tools were questionnaires and interviews that conducted by the university's leadership staffs and data analysis was conducted in 2 ways: Qualitative and Quantitative research method, in which 85 respondents were interviewed. The results shows, from the respondents and interview all 85 people, most of whom are between 20 and 40 years old, with 69 people or 81.17%; There are 71 people who have been teachers for at least 5 years, accounting for 88%; those with a bachelor's degree (about 70%) and a master's degree (about 30%); there are 25 graduates from mathematics teachers or about 31%; 15 graduates from chemistry teachers or 18%; 14 graduates from physics teachers or 17%; 13 graduates from biology teachers or 16%; there are 7 people (equal to 9%) graduated the courses of teaching and there are also 7 people (for administrative staff) graduated other courses; Those who have the number of teaching hours per week from 4 hours to 18 hours are up to 94%; Teachers' opinions on the teaching quality of the Department of Natural Sciences of Teachers Training Colleges are currently at a moderate level.